2011
DOI: 10.1093/jxb/err267
|View full text |Cite
|
Sign up to set email alerts
|

Silver ions disrupt K+ homeostasis and cellular integrity in intact barley (Hordeum vulgare L.) roots

Abstract: The heavy metals silver, gold, and mercury can strongly inhibit aquaporin-mediated water flow across plant cell membranes, but critical examinations of their side effects are rare. Here, the short-lived radiotracer 42K is used to demonstrate that these metals, especially silver, profoundly change potassium homeostasis in roots of intact barley (Hordeum vulgare L.) plants, by altering unidirectional K+ fluxes. Doses as low as 5 μM AgNO3 rapidly reduced K+ influx to 5% that of controls, and brought about pronoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 57 publications
3
32
0
Order By: Relevance
“…3B). We have previously shown that sudden exposure to Ag + causes extensive damage to both major membrane systems (plasmalemma and tonoplast) in barley roots (Coskun et al, 2012). By contrast, we observed no effect of mercury (Hg 2+ ) application on tracer release (Fig.…”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations
“…3B). We have previously shown that sudden exposure to Ag + causes extensive damage to both major membrane systems (plasmalemma and tonoplast) in barley roots (Coskun et al, 2012). By contrast, we observed no effect of mercury (Hg 2+ ) application on tracer release (Fig.…”
Section: Resultsmentioning
confidence: 64%
“…Importantly, this qualifies the use of Hg 2+ as a potential inhibitor of AQPs (see below). With respect to the Ag + -induced stimulation in tracer efflux, this effect allowed for quantification of released substrate (in terms of mmol g -1 root fresh weight) via integration of the 13 N loss and estimated intracellular specific activity, as shown previously (Coskun et al, 2012 ; Fig. 3D).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…4b). Thus, Ag + perturbed the immediate B-deprivation responses of roots observed in the elongation zone, although this treatment might have had some adverse side effects on root cell viability, as suggested in another study on barley (Coskun et al 2012). These results suggested that ethylene mediated the early responses of A. thaliana roots to B deprivation, probably upstream of ROS production.…”
Section: Involvement Of Ethylene In Early Responsesmentioning
confidence: 72%